Study of Zakat Verses as an Instrument for Increasing the Human Development Index - Muhammad Faiz Zidan; Muhammad Misbakul Munir; Huslan Husada (Penerbit Hellow Pustaka, 2024)
This research aims to investigate the role of zakat verses in improving the human development index. Through a content analysis approach, verses related to zakat in the Koran are studied in depth to identify values, principles and guidelines that are relevant to human development. The research results show that the zakat verses provide a strong theological and ethical foundation for the implementation of zakat as an instrument of human development. Proper implementation of zakat can improve social and economic welfare, as well as strengthen key aspects of human development such as education, health and gender equality. This study provides a deeper understanding of the potential of zakat as an effective instrument in increasing the human development index, as well as providing a new view on the integration of religious values ​​in social and economic development.